Analysis of The Individual Health Efforts Quality After Accreditation Assessment at Public Health Centers of Semarang City in 2019 (Public Health Perspective Journal, 2020)
Accreditation is the beginning to improve the quality of services including improving the quality of management and leadership, planning strategies, satisfaction of service users, strengthening coordination between stakeholders and increasing the ability of Human Resources. 37 Semarang City Public Health Centers have been accredited with predicate; 1 Plenary, 4 Main, 23 Intermediate and 9 Basic. The purpose of this study was to analyze the implementation of quality management as a service quality control system in the Semarang City Public Health Center after the accreditation assessment. This type of qualitative research with descriptive analytic design. Data collection techniques with in-depth interviews, observation, and document search. The population is the Public Health Center that passed the plenary and primary accreditation, the sampling technique used was using random sampling. Analysis of the data was using data reduction, data presentation and drawing conclusions which are carried out simultaneously. The results showed that the internal quality instrument of UKP services in health centers after the accreditation assessment was not fully implemented, it was necessary to strengthen commitment, standardize facilities and infrastructure to support clinical services, analysis of human resource adequacy both in quantity and quality, increase in knowledge for employees about the clinical service quality system through regular training and assistance, capacity building of accompanying human resources on accreditation assistance techniques, support from the Department of Health and cross-sectoral, basic document review, restructuring of quality organizations and Public Health Center organization, monitoring and evaluation which is carried out maximally and continuously.